Hepatic and reproductive toxicity of sub-chronic exposure to dichlorvos and lead acetate on male Wistar rats - Wahab Adekunle Oyeyemi; Oore-oluwapo Ololade Daramola; Adeniran Oluwadamilare Akinola; Adeoye Oyewole Idris; Ikponmwosa Aikpitanyi (Asian Pacific Journal of Reproduction, 2020)
Objective: To investigate the hepatic and reproductive toxicity of dichlorvos and lead acetate on male Wistar rats. Methods: Fifteen adult male Wistar rats (170-190 g) were randomly divided into three groups, with 5 rats in each group. Group 1 received 0.5 mL distilled water orally and served as the control group, while groups 2 and 3 were orally treated with 2 mg/kg body weight (b.w.) dichlorvos and 10 mg/kg b.w. lead acetate, respectively, for 55 days. Epididymal sperm, serum follicle stimulating hormone (FSH), luteinizing hormone (LH), testosterone concentrations, testicular 17 β-hydroxysteroid dehydrogenase activity (17β-HSD), androgen receptor expression, aspartate aminotransferase (AST), alanine aminotransferase (ALT), testicular oxidant and antioxidant enzymes were evaluated with standard methods. Results: Sperm count, motility, morphology, FSH, LH, testosterone levels, 17β-HSD, androgen receptor expression, and catalase activity were significantly reduced in the dichlorvos and lead acetate treated groups as compared with the control group (P<0.05). The liver AST, ALT activities and malondialdehyde concentration were significantly increased in the dichlorvos and lead acetate treated groups as compared with the control group (P<0.05). Conclusions: The reproductive and hepatic toxicity activities of dichlorvos and lead acetate in male Wistar rats are similar.